Cochlear Implantation in the Setting of Perioperative Anticoagulation and Antiplatelet Therapy. (15th December 2015) - Hunter, Jacob B.; Carlson, Matthew L.; Sweeney, Alex D.; Tombers, Nicole M.; Wanna, George B.; Driscoll, Colin L. W.; Haynes, David S.
Abstract : Objective: To describe surgical outcomes and perioperative complications in patients taking antiplatelet and anticoagulation medications while undergoing cochlear implantation. Study Design: Case series with chart review. Setting: Two tertiary otologic referral center. Subjects and Methods: Forty‐six adult patients (2005‐2014) who underwent cochlear implantation while on perioperative antiplatelet and/or anticoagulation therapy without interruption. Outcomes included estimated intraoperative blood loss, perception of increased difficulty secondary to bleeding, and postoperative complications attributable to continuing anticoagulation or antiplatelet therapy. Results: The cases of 46 patients (mean age, 69.5 years; 30.2% female) were analyzed. Of these, 39 patients were taking aspirin, 10 warfarin, and 7 clopidogrel. Aside from 3 (6.5%) patients with postoperative bruising without hematoma and 1 patient (2.2%) who reported self‐resolving oral cavity blood, no intraoperative or postoperative complications occurred in any patient that could be ascribed to antiplatelet or anticoagulant use. Conclusion: These data demonstrate that the risk of perioperative complications from continued antiplatelet or anticoagulation therapy is low. For subjects who are at risk of major complications (eg, deep venous thrombosis, pulmonary embolism, myocardial infarction, cerebrovascular accident) from temporary medication cessation, continuing antiplatelet or anticoagulation therapy through the perioperative period is an appropriate strategy.